Using Critical Media Literacy to support English Language Teaching and Practice - Westman, Peter (2019)
Digital media can convey a tremendous amount of linguistic information about discourse patterns and grammatical structures as well as clues about social interaction and values in particular communities. Language students that develop their media literacy skills not only develop useful skills of communication and inquiry, but also enhance their understanding of social and cultural practices which can improve their access to the target language community. Students will often bring with them to the classroom their previous experiences of making meanings using digital tools and in digital environments, so there is a clear need for literacy provision to be better aligned with their practices in everyday life. This paper describes and discusses the outcomes of two different media literacy educational initiatives with ESOL learners at a further education (FE) college in the United Kingdom and university students in Italy. This paper will discuss how activities such as media analysis, curation, and production can be used to enhance English Language teaching and learning. It explains the rationale for focusing on media literacy in the language classroom and how these types of pedagogic activities can contribute to the development of emergent and productive ‘Third Spaces’ (Bhabha, 1994) for learners in different settings.